Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/alcalc/agr131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Baclofen in the Management of Alcohol-Dependent Patients with Psychiatric Comorbidity: A Selected Case Series

Abstract: While more than half the patients reported significant reduction in alcohol use, it is not possible to draw definite conclusions about the effectiveness of baclofen, given that it was combined with other psychiatric and alcohol treatments, and because there was no control or comparison group. We recommend caution when offering baclofen to patients with a history of recurrent overdosing or a history of other substance misuse. When prescribing in conjunction with other medications with CNS depressant action, clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…A series of case reports and observational studies indicated that the administration of high doses of baclofen markedly reduced or completely suppressed alcohol intake in patients affected by AUDs [108,109,110,111,112,115,116] as well as the desire to use cocaine in patients affected by CUDs [137]. In France, although baclofen has not been approved for this treatment, an overwhelming number of patients affected by AUDs ask for and receive high doses of baclofen to treat their disorder [175,176].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of case reports and observational studies indicated that the administration of high doses of baclofen markedly reduced or completely suppressed alcohol intake in patients affected by AUDs [108,109,110,111,112,115,116] as well as the desire to use cocaine in patients affected by CUDs [137]. In France, although baclofen has not been approved for this treatment, an overwhelming number of patients affected by AUDs ask for and receive high doses of baclofen to treat their disorder [175,176].…”
Section: Discussionmentioning
confidence: 99%
“…Three case reports showed that the oral administration of baclofen doses ranging between 75 and 125 mg/day was effective in the treatment of AUDs [108,109,110]. Two other case reports found that baclofen administration (from 30 to 400 mg daily) was also effective in reducing or suppressing alcohol consumption in patients affected by AUDs and other psychiatric illnesses in whom previous treatment with other drugs had been unsuccessful [111,112]. …”
Section: Baclofen and Sudsmentioning
confidence: 99%
“…With recent surge of interest in high-dose Baclofen treatment for alcohol dependence, instances of acute deliberate overdose as a suicide attempt have also been reported in this population especially with co-morbid major psychiatric disorders. (Dore et al, 2011;Franchitto et al, 2014;Pommier et al, 2014;Rolland et al, 2015) The usual symptoms recorded are central nervous system (CNS) suppression, cardiac conduction abnormalities and autonomic disturbances. CNS suppression is generally noticed in about 6-8 hours after over dosage and manifest in the form of coma, flaccidity, hyporeflexia, hypothermia, respiratory suppression, seizures and delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a sample of 132 participants the safety and efficacy of higher doses of baclofen in maintaining abstinence or lower risk drinking over a period of 12 months was confirmed [22]. Abstinence or reduced consumption in eight of twenty-one patients with psychiatric comorbidities was described in a selected case series [23]. In Switzerland, baclofen as an off-license treatment option for alcohol dependence has received broad publicity, following the German publication of Oliver Ameisen's self-reported cure from severe alcoholism [24].…”
Section: Clinical and Experimental Pharmacologymentioning
confidence: 95%